The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1097/hjh.0000000000003248
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived extracellular vesicles correlate with therapy-induced nocturnal blood pressure changes

Abstract: Introduction: Elevated nocturnal blood pressure (BP) is closely associated with increased risk of cardiovascular (CV) events. Circulating extracellular vesicles (EVs) have been proposed as a potential CV risk biomarker and shown to correlate with BP. The present study aimed to assess whether a reduction in BP is paralleled by respective changes in EVs.Methods: Fifty-five hypertensive patients (age: 57.7 AE 14.1 years) were included in the study. EVs and BP were assessed at baseline and at 12 weeks follow-up. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Using gold standard BP evaluation (office and ambulatory BP). we have previously demonstrated a positive correlation between the pEV levels and BP and PWV [ 13 , 14 , 15 ]. Other studies have previously investigated EVs in the context of vascular damage and blood pressure, with a special focus on endothelial-derived EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Using gold standard BP evaluation (office and ambulatory BP). we have previously demonstrated a positive correlation between the pEV levels and BP and PWV [ 13 , 14 , 15 ]. Other studies have previously investigated EVs in the context of vascular damage and blood pressure, with a special focus on endothelial-derived EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Ochiai-Homma et al showed that pendrin in urinary EVs can be a useful biomarker for the diagnosis and treatment of primary aldosteronism, and this finding was supported by studies using a rat model of aldosterone excess [ 46 ]. Lugo-Gavidia et al indicated that circulating platelet-derived EVs were positively associated with nocturnal blood pressure at baseline and therapy-induced blood pressure changes over a 12-week treatment period with ambulatory blood pressure monitoring [ 47 ]. Platelet-derived EVs may provide an integrated measure of blood pressure changes achieved with pharmacotherapy.…”
Section: Introductionmentioning
confidence: 99%